The Unilateral Jumping Structures of the Spotted Lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae): A Highly Functional and Integrated Unit - Xu Chen; Aiping Liang (Biomimetics, 2025)
Previous research on the jumping structures of insects with strong leaping abilities mainly focused on overall jumping mechanisms. Our study reveals that the unilateral jumping structures (UJSs) of L. delicatula has relative functional autonomy. The UJSs consist of three distinct but interconnected parts: (1) energy storage component: it comprises the pleural arch and trochanteral depressor muscles, with the deformation zone extending about two-thirds of the pleural arch from the V-notch to the U-notch; (2) coupling component: made up of the coxa and trochanter, it serves as a bridge between the energy and lever components, connecting them via protuberances and pivots; and (3) lever component: it encompasses the femur, tibia, and tarsus. A complete jumping action lasts from 2.4 ms to 4.6 ms. During a jump, the deformation length of the pleural arch is 0.96 ± 0.06 mm. The angles ∠ct (angle between coxa and trochanter), ∠fp (angle between femur and pleural arch), and ∠ft (angle between femur and tibia) change by 57.42 ± 1.60, 101.40 ± 1.59, and 36.06 ± 2.41 degrees, respectively. In this study, we abstracted the jumping structures of L. delicatula and identified its critical components. The insights obtained from this study are anticipated to provide valuable inspiration for the design and fabrication of biomimetic jumping mechanisms.